The Influence of Carrier on the Critical Phenomena in CO Oxidation over NiO - Vitaly K. Yatsimirsky; Vitaly L. Budarin; Vitaly Y. Diyuk; L.Y. Matzui; M.I. Zacharenko (Adsorption Science & Technology, 2000)
The influence of thermo-exfoliated graphite (TEG) on the catalytic activity of nickel in the CO oxidation process has been investigated. It was shown that nickel supported on the thermo-exfoliated graphite surface was more active catalytically than the bulk metal. Alternate oxidation–reduction on the Ni–NiO phase boundary occurred at temperatures higher than 633 K (Curie temperature of pure nickel). Using a magnetogravimetric method, it was found that the nickel catalyst was transformed by the reaction mixture into a heterophase (Ni/NiO) system both in the presence of a carrier and in its absence. Hence the carrier did not influence the size of the Ni particles. The high catalytic activity of the catalyst supported on graphite may be explained by an increase in the number of Ni particles. Ni/TEG and Ni/NiO samples were studied via X-ray diffraction, Auger spectroscopy and electron microscopy methods.